2008
DOI: 10.1016/j.peptides.2008.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral obestatin has no effect on feeding behavior and brain Fos expression in rodents

Abstract: Obestatin is produced in the stomach from proghrelin by post-translational cleavage. The initial report claimed anorexigenic effects of obestatin in mice. Contrasting studies indicated no effect of obestatin on food intake (FI). We investigated influences of metabolic state (fed/fasted), environmental factors (dark/light phase) and brain Fos response to intraperitoneal (ip) obestatin in rats, and used the protocol from the original study assessing obestatin effects in mice. FI was determined in male rats injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 57 publications
0
17
0
2
Order By: Relevance
“…In addition, although obestatin was initially postulated as the ghrelin antagonistic hormone, nowadays its effect on food intake remains strongly controversial. Specifically, obestatin has been shown to suppress food intake and energy balance in some rodent studies (Zizzari et al 2007, Hassouna et al 2012, Gargantini et al 2013, while no effect has been reported by different studies in rats and mice (Gourcerol & Tache 2007, Kobelt et al 2008.…”
Section: Nonendocrine Actionsmentioning
confidence: 98%
“…In addition, although obestatin was initially postulated as the ghrelin antagonistic hormone, nowadays its effect on food intake remains strongly controversial. Specifically, obestatin has been shown to suppress food intake and energy balance in some rodent studies (Zizzari et al 2007, Hassouna et al 2012, Gargantini et al 2013, while no effect has been reported by different studies in rats and mice (Gourcerol & Tache 2007, Kobelt et al 2008.…”
Section: Nonendocrine Actionsmentioning
confidence: 98%
“…The effects of obestatin on food intake 438 remain controversial . Obestatin has been demonstrated to inhibit food intake in rodents (Zhang et al, 2005;Bresciani et al, 2006;Sibilia et al, 2006;Chartrel et al, 2007;Zizzari et al, 2007;Carlini et al, 2007;Green et al, 2007), whereas several research groups fail to show this anorexigenic effect (Seoane et al, 2006;Gourcerol et al, 2007;Nogueiras et al, 2007;Yamamoto et al, 2007;De Smet et al, 2007;Annemie et al, 2009;Kobelt et al, 2008;Mondal et al, 2008;Unniappan et al, 2008). Obestatin had no effect on body weight (Sibilia et al, 2006;Unniappan et al, 2008).…”
Section: Normal Physiology Of Obestatin and Regulation Of Its Expmentioning
confidence: 99%
“…Although several studies failed to reproduce the anorexigenic actions of obestatin, this peptide, when co-administered with ghrelin, was revealed to be an interesting pharmacological tool with respect to blocking some of the effects of ghrelin. (25) This study showed a significant increase in serum obestatin in patient underwent gastric sleeve at one and three months post operation with a significant difference in serum obestatin between patients and controls. This agreed with Chen CY et al study.…”
Section: IVmentioning
confidence: 55%